ANALISIS DAMPAK PENDAFTARAN TANAH SISTEMATIK TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT DI KOTA DEPOK - Sugiyanto Sugiyanto; Hermanto Siregar; Endriatmo Soetarto (Jurnal Manajemen & Agribisnis, 2008)
This research purposes are (1) to analyze communities perception about land certificate, (2) to analyze determinant factors of communities perception toward systematic land registration, (3) to analyze the impact of systematic land registration toward communities social economic conditions, and (4) to  formulate policy implication which can be improved from execution of systematic land registration and its impact to communities social economic conditions. This research used descriptive statistic and inferensia statistic method through survey approach. Primary data collected using structured interview with questionnaire guidelines from 100 respondent with purposive sampling from Curug Village and Sukatani Village in Cimanggis Subdistrict on Depok Regency. This research used range criteria, ordinal logistic regression, Mann-Whitney Test. The results of this research were: (1) communities perception about land certificates represent that certificate perceived very important for strongest evidence of land ownership, safety, easier sell, higher price. While, land certificate perceived important in credit collateral; (2) factors which significantly influencing communities perception toward systematic land registration were time, cost, and procedure of registering land ownership; (3) the impact of systematic land registration toward community social economics condition were land owner safety, land sell amenity, land price and land tax; (4) The systematic land registration is a  feasible project, but need  improvement in: giving high priority for area with productive agriculture and population with low income, project well planning, optimizing of counselling, prohibiting illegal fee with giving punishment and giving reward for countryside officer which have  the vital role